Efficacy of cyanoacrylate glue in anal fistulas - Shivashanka, Santhosh Chikkanayakanahalli; Nagaraja Nayaka, Aruna Nayaka; Manangi, Mallikarjuna; Rao, Seshagiri; Masanashetty, Srinivas Nanjangud (International Surgery Journal, 2019)
Background: Fistula in ano is a common problem. Surgical techniques such as fistulectomy, fistulotomy were associated with complications like excessive bleeding, infection, recurrence etc. The employment of cyano acrylate glue is one of the newer promising techniques. The aim of this study was to evaluate the efficacy of cyanoacrylate glue in the treatment of anal fistulas. Methods: Study was conducted on patients with fistula-in-ano admitted to various surgical units in hospitals attached to Bangalore Medical College and Research Institute from November 2016 to May 2018. A total of 30 patients fulfilling the criteria were included in the study. Under spinal anesthesia, patients were posted for the procedure. Post operatively the patients were examined every 2 weeks for the first 2 months, and then once every 3 months. If the fistula failed to heal with primary treatment at a 4-week interval, a second glue treatment was performed. Post-treatment the success of the procedure was assessed by the incidence of infection and recurrence. Results: Twenty two patients got healed with primary application with stoppage of any discharge from the fistulous track. Two patients required one more application, and one patient required fistulotomy. One patient developed complex fistulas and had to be treated with colostomy and fistulectomy. 4 patients developed purulent discharge after application of glue and were treated with IV antibiotics and healed completely. Conclusions: Cyanoacrylate glue can be offered as a sphincter sparing alternative to fistulectomy in patients with anal fistulas.